Development of attached growth microbial fuel cell (ag-mfc) for treatment of spent caustic wastewater and energy recovery - Norsafiah, Fazli (2022)
Insufficiently treated wastewater and dependability to fossil fuel as the main source of energy led to serious water pollution and depletion of energy resources problem. Spent caustic wastewater is a highly toxic wastewater generated by the petroleum chemical plants. Due to its noxious properties, it required special management for its disposal. Chemical and thermal treatment methods which produced partial oxidation of spent caustic of wastewater are the common industrial practice. This study aims to produce effective treatment of spent caustic wastewater and energy recovery using Attached Growth Microbial Fuel Cell (AG-MFC). AG-MFC a system integrating the MFCs application with suspended GAC as bacterial attachment medium. The GAC addition into the system allowed the presence of attached biomass which has higher growth rate leading to a higher amount of microorganism. Attached biomass are also more resistant to physical and chemical force. These features improved the biomass adaptability in spent caustic. The study began with determination of optimum GAC dosage whereby 0 g to 25 g of GAC dosage was tested. Then, its optimum operating conditions in terms of Mixed Liquor Suspended Solid (MLSS), Solid Retention Time (SRT) and Organic Loading Rate (OLR) were determined by varying the operating conditions of MLSS from 2500 to 4000 mg/L, SRT from 10 to 30 days and OLR at from 700 to 900 mg COD/L.d. The AG-MFC performance was evaluated based on chemical oxygen demand (COD) and sulfide removal and voltage output. The dominant bacteria attached was identified using the molecular method and their morphology was observed using microscopic analysis. Finally, the COD fractionations of spent caustic wastewater were determined using respirometric analysis and the design parameters that described the biological process in the AG-MFC were determined using Activated Sludge Model No. 1 (ASM1). The finding demonstrated 10 g of GAC its optimum dosage since it produced the highest COD and sulfide removal of 97.56% and 96.25% respectively and high voltage output of 583 mV. Higher GAC addition from 0 to 10 g increased the biomass attached. However, there was excessive microorganisms at GAC dosage of higher than 10 g which was not favourable for the AG-MFC operation. The optimum operating conditions of the AG-MFC were at MLSS of 3500 mg/L, SRT of 20 days and OLR of 700 mg/L.d as AG-MFC possessed highest COD removal trend of beyond than 90% at these conditions. High MLSS and SRT were favourable for AG-MFC operation since a higher MLSS increased the amount of microorganisms and higher SRT prolonged the time for bacteria to reproduce. Higher OLR reduced the AG-MFC removal efficiency due to excessive substrates beyond the degradation capacity of the microorganisms. The AG-MFC biomass was dominated with Proteobacteria, which are Gram-negative and have flagella for mechanical attachment on GAC. Increasing OLR has also increased the slowly biodegradable COD (Xs) fraction which explained the low removal efficiency of AG-MFC at high OLR. From the dynamic simulation, it is found that increasing OLR reduced the maximum specific growth rate of heterotrophic microorganisms (μmaxH) and increased heterotrophic decay (bH). This condition indicated higher new soluble and non-biodegradable fractions generated from the decaying biomass which caused low removal at high OLR. This study has demonstrated AG-MFC capacity in producing complete degradation of spent caustic wastewater and is most suitable to serve as the secondary treatment of spent caustic wastewater in the refinery industry